New interchange 1 : english for international communication Teacher's edition - Richards, Jack C. (USA, New York : Cambridge University Press, 2000)
New interchange is a multi-level course in english as a second or foreign language for young adults and adults. The language used in New Interchange is American English; however, the course reflects the facat that English is the major language of international communication and is not limited to any one country, region or culture.
Contents Introduction 1 Please call me chuck 2 How do you spend your day? 3 How much is it? 4 Do you like jazz? 5 Tell me about your family 6 How often do you exercise 7 We had a great time! 8 How do you like the neighborhood? And others more
Incluye contents
Keywords: ENGLISH -- GRAMMAR; ENGLISH -- TEACHING